2014
DOI: 10.1186/1556-276x-9-609
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of zinc oxide nanostructures on graphene/glass substrate by electrochemical deposition: effects of current density and temperature

Abstract: The electrochemical growth of zinc oxide (ZnO) nanostructures on graphene on glass using zinc nitrate hexahydrate was studied. The effects of current densities and temperatures on the morphological, structural, and optical properties of the ZnO structures were studied. Vertically aligned nanorods were obtained at a low temperature of 75°C, and the diameters increased with current density. Growth temperature seems to have a strong effect in generating well-defined hexagonal-shape nanorods with a smooth top edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…We have also reported the successful growth of vertically aligned ZnO NRs on graphene/glass substrates by ED [30]. It was also confirmed that the optical properties and diameters of the NRs can be effectively controlled by the current density during the deposition process [31]. Moreover, the cone-shaped ZnO NRs/CuO heterojunctions with rectifying behaviors on their J-V curves were successfully grown on the Au seed layers by CBD using Zn(CH 3 COO) 2 · 2H 2 O and copper (II) nitrate trihydrate [Cu(NO 3 ) 2 · 3H 2 O] [32].…”
Section: Introductionsupporting
confidence: 61%
“…We have also reported the successful growth of vertically aligned ZnO NRs on graphene/glass substrates by ED [30]. It was also confirmed that the optical properties and diameters of the NRs can be effectively controlled by the current density during the deposition process [31]. Moreover, the cone-shaped ZnO NRs/CuO heterojunctions with rectifying behaviors on their J-V curves were successfully grown on the Au seed layers by CBD using Zn(CH 3 COO) 2 · 2H 2 O and copper (II) nitrate trihydrate [Cu(NO 3 ) 2 · 3H 2 O] [32].…”
Section: Introductionsupporting
confidence: 61%
“…A significant advantage of this material is that its properties are strongly correlated with its size and morphology. For this reason, zinc oxide particles can be found in the literature in many forms, such as wires, tubes, belts, sheets, and rods [9], on different inorganic [10] or organic [11] substrates. In the case of ZnO application as an antibacterial [12], photocatalytic [13], or sensing material [14], a high surface area is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanostructures have been extensively investigated owing to their remarkable physical and chemical properties that can be exploited in various electronic devices and optoelectronic devices. ZnO nanostructures with various geometrical morphologies have been developed using various synthetic methods, such as chemical vapor deposition [9], the hydrothermal method [10], pulsed laser deposition [11], and furnace and electrochemical deposition [12][13]. Various 1-D ZnO nanostructures, such as nanopins [14], nanorods [15], nanotubes and nanowires [16][17], as well as 2-D ZnO nanosheets [18], nanodiscs and nanoplates [19][20], have been fabricated.…”
Section: Introductionmentioning
confidence: 99%